Thought-Sign-Symbol Cross-Cultural Representations of Religion - Bogucki, Lukasz; Bogucki, Lukasz; Galkowski, Artur; Leone, Massimo (Peter Lang, 2022)
This unique volume focuses on religion and spirituality, along with rituals, practices and symbols, discussed and analysed from a semiotic perspective. It covers both cognitive and social dimensions of religious practices and beliefs, various aspects of spirituality, multiple forms of representation, as well as spheres of religious beliefs and practices. The volume is an outcome of the Signum-Idea-Verbum-Opus project initiated by Umberto Eco s keynote address during his visit at the University of Lódz in 2015. More theoretical insights and further explorations into contemporary semiosphere can be found in Current Perspectives in Semiotics: Signs, Signification and Communication and Current Perspectives in Semiotics: Texts, Genres and Representations, published by Peter Lang.